Environmental sensitivity index maps to manage oil spill risks: A review and perspectives - D'Affonseca, Fernando Mazo; Vieira Reis, Fábio Augusto Gomes [UNESP]; Corrêa, Claudia Vanessa dos Santos [UNESP]; Wieczorek, Arthur [UNESP]; Giordano, Lucilia do Carmo [UNESP]; Marques, Mara Lúcia [UNESP]; Rodrigues, Flávio Henrique [UNESP]; Costa, Daiana Marques [UNESP]; Kolya, André de Andrade [UNESP]; Veiga, Vinicius Mendes [UNESP]; Santos, Sarah Félix [UNESP]; Magalhães, Laila Milani [UNESP]; et al. (Elsevier, 2023)
Environmental sensitivity index (ESI) maps and data are employed worldwide to prepare contingency planning and responses for oil spills. The ESI approach has been successfully applied for various marine and continental shorelines, terrestrial pipelines, and roads. Originally, ESI maps were configured as printed cartographic products. With the incorporation of geographic information systems (GIS), ESI maps gained a digital perspective, allowing static correlations between biological and socioeconomic parameters through various operations and methods. Recently, ESI and simulation approaches have been combined to develop quantitative risk assessments, and artificial intelligence and deep learning algorithms support integrated classifications of sensitivity indices. Although challenging, valuations and vulnerability aspects, such as seasonal and multidimensional approaches, should be considered in ESI maps, as well as the integration of monitoring, detection, decision, and response systems. By incorporating dynamic systems into the approach, ESI maps become a social and environmental sensitivity system (SESS). This paper aims to provide a comprehensive review of the development of the ESI concept and to identify and propose future directions.
Keywords: Environmental sensitivity index (ESI) maps; Oil spill; Social and environmental sensitivity system (SESS); Vulnerability analysis